Profil Kinetik dan Efektivitas Enrofloksasin yang Dikombinasikan dengan BioATP dalam Mengatasi Coxiella burnetii (KINETIC PROFILE AND EFFECTIVITY OF ENROFLOXACINE WITH BIO ADENOSIN TRIPHOSPHATE SUPPLEMENTATION AGAINST COXIELLA BURNETII) - ., Andriyanto; Setiyono, Agus; Rahminiwati, Min; Nuryani, Neni; Patriana, Unang (Jurnal Veteriner; Vol 14 No 3 (2013), 2013)
Coxiella burnetii belongs to rikettsia group living obligate intracellularly and as the agent of zoonosisQ fever. Enrofloxacine is an antibiotic in quinolon group used to treat infection of C. burnetii in chicken,goat, calve, pig, dog, cat,  and horse. From ruminant practical experience, enrofloxacine if combined withBioATP  can enhance the enrofloxacine activity. Research for the effecivity of enrofloxacine and BioATP totreat C. burnetii has never been carried out. The research was conducted to explore effect of enrofloxacinewith supplementation BioATP against C. burnetii. Enrofloxacine pharmacokinetic study was carried outby using simental beef as an experimental animals. The effectivity of BioATP supplementation onenrofloxacine activity to treat C. burnetii was tested by using Vero cell tissue culture. The results showedthat combination of enrofloxacine and BioATP increased kinetic profile of enrofloxacine in term of onset,duration, pharmacology intensity, and bioavailaibility. Enrofloxacine had activity to treat C. burnetii withvalue of minimal inhibitory concentration (MIC) at 1-2 ppm and value of minimal bactericidal concentrationat 4 ppm. Supplementation of BioATP improved the effectivity of enrofloxacine in treating C. burnetii.
Keywords: BioATP, enrofloxacine, kinetics profile, Vero cell, Coxiella burnetii